Criminal Law Protection against Female Workers for Victims of Sexual Violence - Hanifah, Ida (Inspiring Law Journal, 2022)
This research uses the literature research method or library research method, which uses a normative legal research approach or doctrinal legal research, where the law is conceptualized as what is written by law in books with legal systematics in laws and regulations or written laws. The data sources used in this study are primary data, as well as secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. This research uses descriptive analytics, namely research that describes the state of the object or its events without the intention to draw generally accepted conclusions. Based on the analysis of the data carried out, it can be concluded that if harassment abuse has attacked the honor and good name of a worker, the Criminal Code has provided protection against women's vulnerability to the threat of physical and sexual violence that they must face, for sexual violence against female workers, each perpetrator will be sentenced to imprisonment or pay a fine, criminal threats for sexual violence must have severe sanctions or suffering inflicted on a person guilty of committing an act prohibited by criminal law. The Criminal Code as a whole has regulated the types of violence, be it rape and other sexual assaults (articles 285-291). If the perpetrator of sexual violence is a worker, then the protection has been stated in section 158 paragraph 1 of the Manpower Law